Combining Photodeprotection and Ligation into a Dual‐Color Gated Reaction System. Issue 71 (16th October 2020) - Alves, Jessica; Krappitz, Tim; Feist, Florian; Blinco, James P.; Barner‐Kowollik, Christopher
Abstract: We report a photochemical reaction system which requires activation by two colors of light. Specifically, a dual wavelength gated system is established by fusing the visible light mediated deprotection of a dithioacetal with the UV light activated Diels–Alder reaction of an o ‐methylbenzaldehyde with N ‐ethylmaleimide. Critically, both light sources are required to achieve the Diels–Alder adduct, irradiation with visible or UV light alone does not lead to the target product. The introduced dual gated photochemical system is particularly interesting for application in light driven 3D printing, where two color wavelength activated photoresists may become reality. Abstract : One wavelength is not enough : We exploit wavelength selective deprotection and photoligation, establishing a dual color gated strategy for Diels–Alder adduct formation. The visible light activated photoredox deprotection of a dithioacetal generates a UV‐light activated diene, which can be trapped by a dienophile, affording the Diels–Alder adduct only in the presence of visible and UV light.